RADIOGRAPHIC EVOLUTION AND CERVICAL SAGITAL BALANCE OF LAMINOPLASTY VERSUS LAMINECTOMY IN PATIENTS WITH CERVICAL SPONDYLOTIC MYELOPATHY - MILAZZO NETTO,LUIZ CARLOS (2020)
ABSTRACT Objective To compare radiographic findings of patients who underwent laminoplasty and laminectomy with arthrodesis for spondylotic cervical myelopathy. Methods Who were submitted to laminectomy with arthrodesis or laminoplasty to treat cervical spondylotic myelopathy with minimum follow-up of 6 months. The radiographic parameters related to the cervical spine evaluated were C0C2 lordosis (C0C2), cervical lordosis (CL), T1 slope (T1S), thoracic inlet angle (TIA), neck tilt (NT), cervical sagittal vertical axis (CSVA), and T1S – CL mismatch (T1S-CL). Results We evaluated 34 patients, 23 (68%) of whom were men. The mean age was 65 years (SD ± 13). There was no statistical difference in any of the preoperative radiographic parameters. Considering the patients submitted to laminectomy alone, a significant difference was observed for C0C2 (P = 0.045), CSVA (P = 0.0008), with differences between IPO and POS times (P = 0.026) and between PRE and POS (P = 0.0013) and T1S – CL mismatch (P = 0.0004), with a difference between IPO and POS (P = 0.0076) and between PRE and POS (P=0.001). Considering the patients submitted to laminoplasty alone, there was no difference over time for any radiographic parameters considered. Comparing the radiographic parameters between the laminectomy and laminoplasty groups in the three time periods, there was no significant difference for any of them. Conclusion This study suggests that patients with cervical spondylotic myelopathy who underwent laminectomy with instrumentation may present worse radiographic evolution as regards cervical sagittal alignment over time when compared to patients who underwent laminoplasty. Level of evidence III; Retrospective case series.